International, inter-university transferability of a student health surveillance system (SuSy) tool - Ralf Reintjes; Maxine Holt; Alexandra Kalbus; Susan Powell (European Journal of Public Health, 2019)
Introduction While university students are known to face major life transition challenges with the risk to engage in potentially undesirable health-related habits, there are very few attempts to monitor students’ health behaviour on a regular long-term basis. Even in cross-sectional designs, students from the field of Public Health and/or Health Sciences are rarely investigated. Here, a cross-university students’ health behaviour surveillance system is presented. Methods A students’ health and health behaviour surveillance system (SuSy) has been implemented in Hamburg University of Applied Sciences in 2014, collecting and analysing data of health sciences students twice a year since. After Manchester Metropolitan University joined the project and adapted SuSy to its specific context in 2016, data of both SuSy settings were compared using logistic regression models. In addition, focus groups were carried out in both universities in order to assess the perception and acceptance of the tool. Results After eight elicitations with total sample of 1366 responses, a decreasing trend of smoking and increasing trend of cannabis consumption can be observed among Hamburg students. In comparison, Manchester students tend to smoke significantly more (OR = 3.74, 95%CI 1.95-7.17), but consume less cannabis (OR = 0.51, 95%CI 0.14-0.9). Trends in physical activity and healthy food consumption complete the overview. Focus groups revealed that SuSy is perceived as an appealing, useful and recognisable tool among students from both universities. Discussion While being easily adapted in content and delivery, SuSy allows for the provision helpful, comparable information about students’ health behaviours as well as for the observation of time trends. These findings underline SuSy’s potential in promoting university students’ health. Key messages The student health surveillance system (SuSy) tool allows comparable information about students’ health behaviours as well as the observation of time trends. SuSy is perceived as an appealing, useful and recognisable tool among students from both universities.